The Response of Single Crosses to Inoculation with Maize Lethal Necrosis - Cheruiyot, Susan; Kiplagat , Oliver; Leley , Philip (African Journal of Education,Science and Technology (AJEST), 2018)
Maize is by far the most important staple food commodity in many households in Kenya. Maize lethal Necrosis disease has in the recent past become a menace in hindering maize production in many regions of Kenya. A survey was carried out in Naivasha and Bomet to identify MLN resistant single cross genotypes growing under high disease pressure. MLN disease severity and MLN disease incidence was based on symptoms on the plant on a three weeks interval after planting until grain filling stage, plant stand count and yield. The causal pathogen was confirmed by diagnostic tests. There was a significant difference in resistance levels at p≤0.05 among the single cross varieties with respect to MLND. The scores ranged from 2.8- 3.9 in the two locations. Naivasha had higher disease scores with most severe symptoms in line SC-MLN-15-1 with a score of 4.0. Lines SC-MLN-15-6, SC-MLN-15-6, SC-MLN-15-7, SC-MLN-15-8, SC-MLN-15-15 and SC-MLN-15-37 showed moderate resistance. Lines SC-MLN-15-3 and SC-MLN-15-56 exhibited moderate resistance. High variability of MLN response was observed among the 120 maize genotypes indicating the exisistence of potential useful germplasm for improving MLN resistance for breeding programmes. It is concluded that MLN is still a persistent problem with high incidence associated with growing susceptible varieties, recycling hybrid seed and presence of alternative hosts for insect vectors; however resistant genes could be obtained from maize genotypes showing lower disease severity in these regions which have a high disease pressure which is a crucial strategy to ensure safe production of maize in the region